The clinical utility of renal concentrating capacity in polycystic kidney disease - Gabow, Patricia A.; Kaehny, William D.; Johnson, Ann M.; Duley, Irene T.; Manco-Johnson, Michael; Lezotte, Dennis C.; Schrier, Robert W. (Kidney international, 1989)
The clinical utility of renal concentrating capacity in polycystic kidney disease. We studied 177 adult nonazotemic subjects with autosomal dominant polycystic kidney disease (ADPKD) and 123 unaffected family members (NADPKD). In order to assess the factors influencing renal concentrating capacity maximal urinary osmolality (UOsm) after overnight water deprivation and vasopressin was measured. UOsm was reduced in ADPKD (680 ± 14) compared to NADPKD subjects (812 ± 13 mOsm/kg). A greater severity of the architectural abnormality as assessed by cyst number and size and remaining volume of normal parenchyma was associated with a greater impairment of renal concen trating capacity. The concentrating defect was present in the youngest ADPKD subjects and the rate of decline of concentrating capacity with age in ADPKD paralleled that in NADPKD subjects. Based on the initial 135 subjects studied, we developed an algorithm for diagnostic screening for ADPKD utilizing blood pressure, serum creatinine and UOsm designed to maximize sensitivity. When applied to a subsequent population of 165 adults, 121 with ADPKD and 44 unaffected relatives, this algorithm would have spared 20% of unaffected subjects from the cost of ultrasound while failing to detect less than 2% of affected subjects. This simple protocol thus offers a rapid and inexpensive way to screen for ADPKD.